2014
DOI: 10.1128/cvi.00275-14
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Randomized Double-Blind Study of the Safety and Immunogenicity of a Nonadjuvanted Vero Cell Culture-Derived Whole-Virus H9N2 Influenza Vaccine in Healthy Adults

Abstract: dStudies on candidate pandemic vaccines against avian influenza viruses have focused on H5N1, but viruses of other subtypes, such as A/H9N2, are also considered to have pandemic potential. We investigated the safety and immunogenicity of two immunizations with one of five different antigen doses (ranging from 3.75 to 45 g of hemagglutinin antigen) of a nonadjuvanted whole-virus G9 lineage H9N2 influenza virus vaccine in healthy adults aged 18 to 49 years. The antibody responses were measured by hemagglutinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…It has been proposed that despite the fact that influenza type A and type B are structurally and functionally similar, they show fundamental differences in the ways in which the host recognizes these pathogens [3]. In this study, the aim was to determine factors that influence the preferential isolation of influenza type B [3], a finding supporting the faster restriction and clearance of influenza type B virus.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It has been proposed that despite the fact that influenza type A and type B are structurally and functionally similar, they show fundamental differences in the ways in which the host recognizes these pathogens [3]. In this study, the aim was to determine factors that influence the preferential isolation of influenza type B [3], a finding supporting the faster restriction and clearance of influenza type B virus.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the aim was to determine factors that influence the preferential isolation of influenza type B [3], a finding supporting the faster restriction and clearance of influenza type B virus. The IRF 3 is part of a large transcription factor family which has IRF 1 -9, and these are involved in regulation of cell cycle, apoptosis and tumor suppression [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, additional models mimicking natural infection are required for evaluation of the pathogenicity of H9N2 virus. Several trials of inactivated and live attenuated vaccines against H9N2 virus in mice and humans have been reported . We previously reported that whole particle vaccines prepared from a virus library that contained 144 combinations of 16 HAs and 9 neuraminidases (NAs) conferred protective immune responses against H5N1 and H7N7 highly pathogenic influenza viruses in cynomolgus macaques .…”
mentioning
confidence: 99%